INVESTIGATION ON DESIGN AND FABRICATION OF TWO HALF LAMINATED SLEEPERS IN COMPARION WITH CONVENTIONAL TYPE - Habibalah Arabtabar (Regional Information Center for Science and Technology (RICeST), 2001)
The economical importance of railroads and their development in Iran have been caused those annually 500000 wood sleepers to be required, if sleepers are to be maintained in suitable condition. However, the wood resources are also limited, specially producing roadbeds with high classes. For conservation of natural resources (Forests) we need to use logs with lower classes as well. The process of lamination can permits manufacturing sleepers from small logs. Therefore, the manufacturing of two half laminated ties (interface vertical or horizontal) were lower. As in Iranian beech is usually used for manufacturing sleepers, in this study it was also utilized to make dowel-laminated sleepers. The results of this study showed that, the processes of impregnation of dowel-laminated sleepers with preservative (Creosote) and depth of its penetration were better established than in usual sleepers. Laboratory test indicated that modulus of elasticity of two half laminated - vertical sleepers was the same as the usual sleepers but this resistance in two half laminated - horizontal sleepers was decreased. Finally after five years exposure under extensive service, tests no failures in dowel-laminated sleepers especially in vertical shapes were observed.